Pengaruh Keragaman Produk, Diskon, Store Atmosphere Dan Citra Toko Terhadap Loyalitas Pelanggan - Wiwit Yuliasari Nurul rizka Arumsari Rhealin Hening Karatri (Jurnal Ekonomi dan Bisnis (EK dan BI), 2023)
This research aims to analyze the influence of product diversity, discounts, store atmosphere and store image on customer loyalty. The sampling method in this research is a non-probability sampling technique, with incidental sampling type. The results of this research show that partially product diversity and store image have a positive and significant effect on customer loyalty, but discounts and store atmosphere have an insignificant positive effect on customer loyalty. Meanwhile, product diversity, discounts, store atmosphere and store image simultaneously affect customer loyalty.